Collaborative project-based learning: an integrative science and technological education project - Baser, Derya; Ozden, M. Yasar; Karaarslan, Hasan (Routledge Journals, Taylor & Francis Ltd, 2017)
Background: Blending collaborative learning and project-based learning (PBL) based on Wolff (2003) design categories, students interacted in a learning environment where they developed their technology integration practices as well as their technological and collaborative skills.Purpose: The study aims to understand how seventh grade students perceive a collaborative web-based science project in light of Wolff's design categories. The goal of the project is to develop their technological and collaborative skills, to educate them about technology integration practices, and to provide an optimum collaborative, PBL experience.Sample: Seventh grade students aged 12-14 (n=15) were selected from a rural K-12 school in Turkey through purposeful sampling.Design and methods: The current study applied proactive action research since it focused on utilizing a new way to enhance students' technological and collaborative skills and to demonstrate technology integration into science coursework. Data were collected qualitatively through interviews, observation forms, forum archives, and website evaluation rubrics.Results: The results found virtual spaces such as online tutorials, forums, and collaborative and communicative tools to be beneficial for collaborative PBL. The study supported Wolff's design features for a collaborative PBL environment, applying features appropriate for a rural K-12 school setting and creating a digitally-enriched environment. As the forum could not be used as effectively as expected because of school limitations, more flexible spaces independent of time and space were needed.Conclusions: This study's interdisciplinary, collaborative PBL was efficient in enhancing students' advanced technological and collaborative skills, as well as exposing them to practices for integrating technology into science. The study applied design features for a collaborative PBL environment with certain revisions.
Keywords: Technology integration; science; collaborative learning; project-based learning; IT